Evaluating the effectiveness of an Android-based English e-module on senior high school students’ interest and achievement - Yosa Novia Dewi; Yenni Rozimela; M Zaim (Universitas Syiah Kuala, 2026)
In the context of globalization and the rapid development of information and communication technology, mastering English has become an essential skill for high school students in Indonesia. However, students’ interest in learning and achievement in English is still below international standards. This research aims to develop and evaluate the validity, practicality, and effectiveness of an Android-based English e-module in increasing students’ learning interest and outcomes. This research uses a quantitative approach with a one-group pretest-posttest pre-experimental design. The e-module was developed using the 4D model (Define, Design, Develop, and Disseminate) and implemented with 90 tenth-grade students and six English teachers from three high schools in Pariaman, Indonesia. Data was collected through expert validation instruments, practicality questionnaires, learning interest questionnaires based on the ARCS model, and English language learning outcome tests covering listening, speaking, reading, and writing skills. The research results show that the e-module has a very high validity level (89.75%) and is considered very practical by students (81.90%) and teachers (90.40%). Students’ learning interest is in the high category (average 84%) with a large effect size (Cohen’s d=0.87). English language learning outcomes also increased significantly (p<0.001), with a moderate N-Gain score (0.63) and a large overall effect size (Cohen’s d=0.85). Although this study has limitations in terms of implementation duration and synchronous interaction, the findings indicate that the Android-based English e-module effectively supports student-centered English language learning at the high school level.